Analisis Dampak Perilaku Bullying Terhadap Hasil Belajar Siswa Kelas V SD Kayuapu - Oktaviana Annisa Zahra; Feri Ariyani; Lovika Ardana Riswari (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
This research was motivated by students who experienced bullying and affected learning outcomes. The purpose of this study is to describe the analysis of the impact of bullying on the learning outcomes of grade V students of SD Kayuapu. The type of research used is qualitative descriptive research. This type of data collection consists of interviews and observations. Analysis of data used in research is carried out through the use of data reduction systems, data presentation, and conclusions. The stages used in this study are the stages of preparation, implementation, and data analysis. Based on the results of the study, it was found that there are three dimensions of student learning difficulties. that is, in the school environment and home environment. In the school environment, students feel afraid to be near their classmates. This is because the student is under pressure from several other students in the form of verbal bullying. The second is that student learning motivation is disrupted due to the bullying they face, making students feel alone and have no learning motivation or learning encouragement from those around them, the third One of the important impacts in mental health is that students tend to be quiet, keep their distance, and prefer not to mingle with their friends